2020
DOI: 10.3390/vetsci7030133
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Processing of Clarias gariepinus (Burchell, 1822) Filets: Insights on the Nutritive Value and Organoleptic Parameters

Abstract: This study evaluated the effects of cooking for different hydrothermal-treatment durations (10, 20, 30 and 40 min) on the proximate composition, amino acid profile, fatty acid composition and organoleptic parameters of filets of African catfish Clarias gariepinus (Burchell, 1822). Filets of the fish were prepared from market size African catfish with similar breeding history. Parameters of the processed filet under the different hydrothermal durations were also compared against a raw–unprocessed control group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…Therefore, it could be concluded that the gradual decrease in colour, taste, flavor, juiciness and overall acceptability scores throughout the storage period at deferent temperatures, could be attributed to the protein denaturation, hydrolysis and fat oxidation, which are the major factors of changes in Organoleptic properties during storage periods these results are agreement with those given by Schubring, Raju, C. V, Darweash BM., Okomoda VT [18,6,7,23].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it could be concluded that the gradual decrease in colour, taste, flavor, juiciness and overall acceptability scores throughout the storage period at deferent temperatures, could be attributed to the protein denaturation, hydrolysis and fat oxidation, which are the major factors of changes in Organoleptic properties during storage periods these results are agreement with those given by Schubring, Raju, C. V, Darweash BM., Okomoda VT [18,6,7,23].…”
Section: Discussionmentioning
confidence: 99%
“…Filleting was done by four skilled fish processors. The procedure for filleting was according to the report of Yenmak et al (2018) following the few modifications made by Okomoda et al . (2020) .…”
Section: Methodsmentioning
confidence: 99%
“…One of the most important health benefits of eating fish is its complex fatty acid profile [40]. Saturated fatty acids (SFA), monounsaturated fatty acids (MUFA), and polyunsaturated fatty acids (PUFA) are defined.…”
Section: Fatty Acid Content Of Catfish Meatmentioning
confidence: 99%